2016
DOI: 10.1038/srep37411
|View full text |Cite
|
Sign up to set email alerts
|

Tet1-dependent epigenetic modification of BDNF expression in dorsal horn neurons mediates neuropathic pain in rats

Abstract: Ten-eleven translocation methylcytosine dioxygenase 1 (Tet1) mediates the conversion of 5-methylcytosine (5 mC) to 5-hydroxymethylcytosine (5 hmC), hence promoting DNA demethylation. Although recent studies have linked the DNA demethylation of specific genes to pain hypersensitivity, the role of spinal Tet1-dependent DNA demethylation in nociception hypersensitivity development remains elusive. Here, we report correlated with behavioral allodynia, spinal nerve ligation (SNL) upregulated Tet1 expression in dors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 55 publications
(82 reference statements)
3
49
0
Order By: Relevance
“…Recent work suggests the involvement of TET1 in pathological pain. TET1 is expressed exclusively in the neurons of the DRG and spinal cord dorsal horn [34,35], 2 major pain-related regions in the nervous system. Peripheral SNL and paw injection of formalin or complete Freund's adjuvant (CFA) increased TET1 expression in ipsilateral spinal cord dorsal horn, but not in the DRG [14,[34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work suggests the involvement of TET1 in pathological pain. TET1 is expressed exclusively in the neurons of the DRG and spinal cord dorsal horn [34,35], 2 major pain-related regions in the nervous system. Peripheral SNL and paw injection of formalin or complete Freund's adjuvant (CFA) increased TET1 expression in ipsilateral spinal cord dorsal horn, but not in the DRG [14,[34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…TET1 is expressed exclusively in the neurons of the DRG and spinal cord dorsal horn [34,35], 2 major pain-related regions in the nervous system. Peripheral SNL and paw injection of formalin or complete Freund's adjuvant (CFA) increased TET1 expression in ipsilateral spinal cord dorsal horn, but not in the DRG [14,[34][35][36][37][38]. Knockdown of spinal TET1 alleviated the formalin-, CFA-, and SNL-induced nociceptive behaviors through blocking TET1-triggered expression of dorsal horn miR-365, Stat3, and BDNF, respectively [35,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Louisa et al reported that TET1 directly binds to the promoter of insulin‐like growth factor 2 mRNA binding protein 1 (IGF2BP1) and influences the DNA hydroxymethylation status of its promoter, which can contribute to the stemness of human mesenchymal stem cells. Knocking down the rat spinal TET1 decreased 5hmC enrichment and further increased 5mC enrichment on the promoter CpG sites of the brain‐derived neurotrophic factor gene, attenuating its expression . Given that the expression pattern of FAM20C and the effect of FAM20C depletion on the odontoblastic differentiation of hDPCs were quite similar to those of TET1 and that FAM20C with a putative long CGI in its promoter is thought to be one of the potential TET1‐occupancy genes in Mus musculus, we were prompted to explore the possibility that TET1 might regulate FAM20C transcription through its hydroxymethylation status in hDPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Knocking down the rat spinal TET1 decreased 5hmC enrichment and further increased 5mC enrichment on the promoter CpG sites of the brain-derived neurotrophic factor gene, attenuating its expression. 45 Given that the expression pattern of FAM20C and the effect of FAM20C depletion on the odontoblastic differentiation of hDPCs were quite similar to those of TET1 and that FAM20C with a putative long CGI in its promoter is thought to be one of the potential TET1-occupancy genes in Mus musculus, we were prompted to explore the possibility that TET1 might regulate FAM20C transcription through its hydroxymethylation status in hDPCs. Our results revealed that TET1 deficiency with no compensatory upregulation of TET2 or TET3 led to significantly reduced odontoblast marker expression and a concomitant reduction in FAM20C levels.…”
Section: Discussionmentioning
confidence: 99%